Speech Errors as Linguistic Evidence 1984
DOI: 10.1515/9783110888423.164
|View full text |Cite
|
Sign up to set email alerts
|

Spoonerisms: The Structure of Errors in the Serial Order of Speech

Abstract: Abstract-Spoonerisms are defined as involuntary rearrangements of elements in the serial order of speech, as when waste the term is produced as taste the werm. An analysis of 124 Spoonerisms in the natural speech of Germans showed that:1. Identical phonemes usually preceded (or followed) the reversed phonemes. 2. Reversals preceding identical phonemes were as common as reversals following identical phonemes. / 3. Reversed phonemes usually had similar articulatory form, i.e. voicing, nasality, open ness, and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thus, as noted previously, many typographical errors can be attributed in part to slips of the tongue, but that only begs the question of why such slips occur. That question is presumably in the province of psycholinguists, and provocative accounts are available (e.g., Baars, 1980, 1992b; Dell & Reich, 1980; MacKay, 1970, 1973; Nooteboom, 1973; van den Broecke & Goldstein, 1980). It is worth noting that Fromkin (1973) found that vowels do not switch with consonants, that Laver (1980) has attributed vowel speech errors to neuromuscular processes, and that Wicklegren (1965) found that errors in short-term memory are related to phonetic similarity, especially with vowels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as noted previously, many typographical errors can be attributed in part to slips of the tongue, but that only begs the question of why such slips occur. That question is presumably in the province of psycholinguists, and provocative accounts are available (e.g., Baars, 1980, 1992b; Dell & Reich, 1980; MacKay, 1970, 1973; Nooteboom, 1973; van den Broecke & Goldstein, 1980). It is worth noting that Fromkin (1973) found that vowels do not switch with consonants, that Laver (1980) has attributed vowel speech errors to neuromuscular processes, and that Wicklegren (1965) found that errors in short-term memory are related to phonetic similarity, especially with vowels.…”
Section: Discussionmentioning
confidence: 99%